Using a range of methods to access children's voices. - Mc Carron, Mary (My University, 2013)
The purpose of this paper is to describe, and reflect upon, a number of methods deployed to facilitate sick children to have a voice within an acute health care setting. Using an ethnographic approach to investigate the nature of communication between children and health professionals, multiple modes of data collection were employed to engage children's interest, motivation and facilitate child empowerment in the process. The simultaneous use of semi-participant observations, informal interviews and participatory activities ensured that the diverse abilities, interests and preferences of children were acknowledged. Multiple data sources permitted the portrayal of a comprehensive picture which we believe enhanced the trustworthiness of the data. However, as with all data collection methods, researchers need to be critically aware of strengths and weaknesses and these will be reflected upon. Ultimately, it was crucial to use participatory activities in context and have continuous dialogue with the participating children. The goal was to achieve a balance between creative instruments and commonplace conversation. We believe the unstructured and flexible approach, and variety of data collection methods, utilised in our study enhanced its accuracy, truthfulness and reduced the subjectivity of children's responses. In sharing our experiences, we endeavour to assist other researchers in conducting research with children.
PUBLISHED
Keywords: Health; Children; Ageing; Identities in Transformation